THE SPREAD OF PUBLISHING HOUSE PRODUCTION OF LITHUANIAN UNIVERSITIES - USAVIČIENĖ, DANGUOLĖ (Knygotyra, 2014)
Distribution of publications by university publishers is considered one of the most complicated spheres of publishing activities because of its particularities. It requires not only attention (support) from the State, but also much effort from the publisher. Today we often stress the status of the university, development of possibilities of the academic publisher and distribution of scientific publications. It makes us think of the relationship between commercial and noncommercial activity in cultural space and discuss effectiveness of distribution of academic books and communication.It should be stressed that from the scientific point of view distribution of publications of university publishers is still an unexplored sphere. We lack theoretic literature and relevant information. There is almost no information about the distribution of publications delivered by university publishers. Our research involved 15 state university publishing houses that were financed by the state budget. The research was based on archival documents, data basis of university publishers, etc. (press, virtual space). The method of interview was chosen (a halfstandardized interview). People from university publishing houses responsible for distribution were interviewed (15 persons) and a questionnaire was made up (24 open questions). The research revealed their possibilities and attitude towards the distribution of books.The aim of the article was to investigate the space of production distribution within the university and outside it in order to reveal particularities of this distribution. The distribution analysed covers the period 1991–2011, but the main attention was paid to book distribution in the recent years in order to stress the importance of the present situation experienced by university publishers. The first part of the article looks for the answer whether university publishers have any model of book distribution. After determining relations among the elements of distribution structure, the scheme of the system of book distribution was established. The second part investigates the situation from an outward perspective, namely, exploring how university publishers are able to use the possibilities of free-market, looking for distribution methods, ways and forms as well as highlighting some peculiarities of distribution of academic books.It was found that the distribution space of publications delivered by contemporary university publishers could be divided into two groups. The first group covers non-commercial distribution system inside the university that was formed in the long-term book distribution culture and experience gained by university publishers. The second group is related to commercial distribution system outside the university that for a long time had been closed; only now it is little by little directed towards commercialization. This shows that in the twenty years of the Independent Lithuania, university publishers have experienced some changes in the distribution of their books. These changes were determined by political and economical conditions, fast development of information and communication technologies and alternations of public communicational processes.Summarising the research, peculiarities of book distribution by university publishers must be stressed. These peculiarities determine the particularity of this distribution process, distinguishing the following three dominating components: scientific product (specific item), institution (departmental subordination), the publisher‘s initiative (the need to change). These components make the basis of the general distribution of publications by university publishers.